Responsible Boating Protects Coral Reefs - Ana Zangroniz; Savanna C. Barry; Joy Hazell (EDIS)
This document gives an introduction to the corals and coral reefs of Florida. Ecological and economic information is given, as well as steps to ensure that safe boating practices reduce physical impacts of coral reefs.